Colombia : Financial Sector Assessment Program-Technical Note on Macroprudential Framework Policy and Tools. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
There has been little change in the institutional framework for macroprudential policy oversight since the last FSAP. Macroprudential policy for the banking sector is a shared competency of the Financial Superintendency of Colombia (SFC), the Banco de la Republica (BR), and the Ministry of Finance (MHCP), although the SFC and the MHCP play dominant roles. The Financial Sector Coordination and Monitoring Committee (CCSSF), which consists of the three institutions and the Financial Institutions Guarantee Fund (Fogafin), is the main platform for information sharing and cooperation, but it does not have a macroprudential mandate or any formal powers. The SFC supervises asset managers and insurance companies, but there is no formal macroprudential oversight framework for those types of financial institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Colombia